Nontoxigenic Vibrio cholerae Septicemia in an Immunocompromised Patient. (10th July 2012) - Kadkhoda, Kamran; Adam, Heather; Gilmour, Matthew W.; Hammond, Gregory W.
Abstract : We report a recent case of non-O1, non-O139, nontoxigenic Vibrio cholerae septicemia in a post-liver-transplant immunocompromised patient associated with prior seafood consumption. Non-O1, non-O139 V. cholerae strains have been reported in several cases of extraintestinal infections and seem to be emerging infectious agents especially in patients with immunocompromising conditions.